REPRESENTASI CORE VALUE “LIFE” PADA PERANCANGAN ASET GRAFIS JAKARTA INTERNATIONAL UNIVERSITY SEBAGAI BAGIAN DARI CORPORATE IDENTITY - RIhi, Samuel (JURNAL Dasarrupa: Desain dan Seni Rupa, 2024)
This study focuses on the representation of the core value "LIFE" (Love, Integrity, Faithfulness, Excellence) in the design of graphic assets for Jakarta International University (JIU) as part of the university's corporate identity. Utilizing a qualitative research method, the study explores how graphic assets, such as patterns, contribute to strengthening JIU's visual identity and brand. The findings indicate that graphic pattern designs reflecting the core value "LIFE" create a consistent and easily recognizable visual impression. These signature patterns not only enhance JIU's visibility and reputation but also serve as visual elements that reflect the university's character and core values. Additionally, patterns designed based on the core value "LIFE" help distinguish JIU from other institutions, while also increasing its appeal within academic circles and the wider community. This design process serves as an example of the exploration of graphic asset utilization for branding purposes, aimed at promoting the "LIFE" core values not only within the JIU academic community but also to the general public.